Perbandingan Kinerja Keuangan dari Koperasi unit desa Sawit Raya, Sawit Mekar Jaya,dan Sawit Abadi Kabupaten Sambas - Edy Suryadi; Bambang Widadi (Universitas Muhammadiyah Pontianak, 2013)
The purpose of this study was to compare the financial performance of the three Koperasi Unit Desa (KUD), namely Sawit Jaya, Sawit Mekar Jaya, and Sawit Abadi, in Sambas district. The method used is to calculate financial ratios by cross sectional method approach. Data obtained from the company's financial statements for the years 2009-2011. Based on calculations from 2009 - 2011, liquidity, profitability, and solvency ratios of the KUD Sawit Jaya better than KUD Sawit Mekar Jaya dan Sawit Abadi. As for the ratio of the activity, KUD Sawit Abadi better as compared to other cooperatives.Keywords: Kinerja Keuangan, Rasio Likuiditas, Rasio Profitabilitas, Rasio Solvabilitas, Rasio Aktivitas.